HUBUNGAN KESEJAHTERAAN PSIKOLOGIS DENGAN KOMPETENSI PROFESIONAL GURU PAUD DI KELURAHAN TAMANSARI KECAMATAN BANDUNG WETAN KOTA BANDUNG - Hermayanti Purnama Sari 10030222033; Nan Rahminawati; Nurul Afrianti (Bandung Conference Series: Early Childhood Teacher Education, 2026)
This study aims to determine the levels of psychological well-being and professional competence, as well as the relationship between these two variables, among early childhood education (PAUD) teachers in Tamansari Urban Village, Bandung Wetan District, Bandung City. The study employs a quantitative approach using a correlational method. The sample consists of 48 PAUD teachers, selected using a saturated sampling technique. Data were collected via a Likert-scale questionnaire that had undergone validity and reliability testing. Data analysis involved descriptive analysis, normality testing, linearity testing, Pearson Product-Moment correlation analysis, and the calculation of the coefficient of determination. The results indicate that the levels of psychological well-being and professional competence among the PAUD teachers fall into the moderate category. Furthermore, a positive and significant relationship exists between psychological well-being and professional competence. These findings suggest that teachers with higher levels of psychological well-being tend to possess higher levels of professional competence. Therefore, enhancing teachers' psychological well-being should be a priority in efforts to support the development of professional competence among PAUD teachers.